Peran red flags terhadap pengaruh skeptisisme profesional, pengalaman kerja dan beban kerja auditor terhadap kemampuan auditor mendeteksi fraud - Indah Masri; Yetty Murni; Amelia Oktrivina; Elsa Maura Adhianti (LPMP Imperium, 2022)
This study aims to see the role of red flags as a moderating variable of professional skepticism, work experience, and workload on the auditor's ability to detect fraud on a survey conducted in several public accounting firms in Jakarta. This study uses primary data to analyze and evaluate the questionnaires distributed to 50 auditors as respondents. Data analysis using PLS-SEM proves that only work experience has a significant positive effect at the 5% level on the auditor's ability to detect fraud. Meanwhile, the red flag has a significant positive effect at the 5% level as a moderating variable to weaken the negative effect of workload on the auditor's ability to detect fraud. Implications and suggestions are explained in the article